KEMAMPUAN PENGGUNAAN BAHASA BAKU MAHASISWA PROGRM STUDI BAHASA INDONESIA IKIP SILIWANGI DI MEDIA SOSIAL INSTAGRAM - Yulianti Nuryastini; Ajeng Rita Nurdian; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This article describes the results of research on the use of standard language among Indonesian Language students IKIP Siliwangi. This research is motivated by the number of writing captions on instagram that do not pay attention to the standard language in accordance with the rules of language. The purpose of this study was conducted to determine the ability of students of Indonesian Language Study Program IKIP Siliwangi in standard language skills. which is focused on this research is the writing of my language in instagram caption. The results showed only 13.8% of students using standard language in writing the standard language and 86.2% of students do not use standard language in writing captions in instagram. This result shows that the ability to use standard language among Indonesian students of IKIP siliwangi is still low and there needs to be an increase in interest in improving the habit of writing standard language either especially in writing captions in instagram.